PENGARUH KEMASAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MIE SEDAAP (STUDI KASUS KELURAHAN CINTA DAMAI MEDAN HELVETIA) - Eka Dewi Setia Tarigan; Eka Putra (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
This research heads for (1) knowing the influences of the packaging to the consumerbuying decision (2) to know influence of the pricing to the consumer buyingdecision. (3) to know influences of the packaging and price to the consumer buyingdecision. The study was conducted to 2400 respendents representing the buyerpopulation mi Sedaap in Kelurahan Cinta Damai Of Medan. Simultantly thisresearch head for knowing the influences of packaging and price to the buyerdecisions.Keywords:Packaging, price and consumer buying decision